The rural-urban dialectic in pre-monarchic Israel : Israel vis-a-vis the Canaanites and the Philistines, ca. 1200 to 1020 B.C.E - Germond, Paul Andre (Department of Religious Studies, 2016)
Bibliography: pages 123-136.